The politics of the administrative process - Kettl, Donald F. (Los Angeles : SAGE/CQ Press, 2012)
Looking closely at policymaking and politics, this Fifth Edition has been substantially updated to provide readers with up-to-date research, data and case studies on the U.S. administrative process.
AccountabilityPART ONE: THE JOB OF GOVERNMENTWhat is Public Administration?What Government Does-And How It Does ItPART TWO: ORGANIZATIONAL THEORY AND THE ROLE OF GOVERNMENT'S STRUCTUREOrganizational TheoryThe Executive BranchOrganization ProblemsAdministrative ReformPART THREE: PEOPLE IN GOVERNMENT ORGANIZATIONSThe Civil ServiceHuman CapitalPART FOUR: MAKING AND IMPLEMENTING GOVERNMENT DECISIONSDecision MakingBudgetingImplementationPART FIVE: ADMINISTRATION IN A DEMOCRACYRegulation and the CourtsExecutive Power and Political Accountability
Includes bibliographical references (p. 517-563) and index.
Keywords: Public administration -- United States -- Textbooks